2011
DOI: 10.1002/jid.1656
|View full text |Cite
|
Sign up to set email alerts
|

Aid and tax revenue: Signs of a positive effect since the 1980s

Abstract: This paper addresses the effect of aid loans and grants on tax effort using data for 82 developing countries over 1970–2005. We find no robust evidence for a negative effect of aid (grants or loans) on the tax/GDP ratio, other than a contemporaneous correlation, but find some evidence that the effect of grants on tax revenue is positive (if significant) since the mid 1980s and that grants tend to increase tax revenue over the medium term. For poor aid recipients, grants are to be preferred to loans because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 23 publications
3
109
2
Order By: Relevance
“…Among recent studies, Gupta (2007) and Teera and Hudson (2004) report a negligible impact of aid on total government revenue, Clist and Morrissey (2011) report no robust negative relationship, and a possible positive impact of aid on taxation since 1985. Brun, Chambas and Guerineau (2009) report that the impact of aid on tax effort is contingent on institutions, with a negative impact in weak institutional environments, but a positive effect in developing countries with stronger institutions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among recent studies, Gupta (2007) and Teera and Hudson (2004) report a negligible impact of aid on total government revenue, Clist and Morrissey (2011) report no robust negative relationship, and a possible positive impact of aid on taxation since 1985. Brun, Chambas and Guerineau (2009) report that the impact of aid on tax effort is contingent on institutions, with a negative impact in weak institutional environments, but a positive effect in developing countries with stronger institutions.…”
Section: Discussionmentioning
confidence: 97%
“…However, while these findings of a negative relationship have received significant attention, other recent studies have found that aid has been associated with a negligible, or even positive, effect on levels of tax collection (Gupta 2007, Brun, Chambas and Guerineau 2009, Teera and Hudson 2004, particularly since 1985 (Clist and Morrissey 2011). These cross-country results are echoed by a range of studies that examine the fiscal effects of aid by considering the relationship between aid, domestic revenue (taxes) and government spending (and sometimes borrowing), usually for a specific country.…”
Section: Aid and Tax Effort: Existing Findings Challenges And Debatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the outcome of these studies are inconclusive, and leads many scholars such as Brun et al (2011a) to suggest that heterogeneity across countries and over time may matter for the relationship between aid and tax revenue. Clist and Morrissey (2011) provide evidence that when considered in lagged values, aid variables become statistically insignificant. Further, Morrissey et al, (2014) find evidence of no consistent cross-relationship between aid and tax effort.…”
Section: Interaction Between Development Aid and Government Public Rementioning
confidence: 90%
“…This result is explained by the fact that aid can improve the effectiveness of public administrations in order to compensate for the negative effect due to additional funding. More recently, Clist and Morrissey (2011) distinguish the specific effects of loans and grants on taxation using panel data find no robust evidence that grants have a negative effect on tax revenue, but identify a positive effect of loans. Finally, Prichard, Brun and Morrissey (2012) argue that understanding the impact of aid on taxation ideally requires information about the whole budget process, including spending, as these studies commonly find that among budget components the tax to GDP ratio varies the least (in technical terms it is exogenous, or not determined by the other variables in the fiscal system; in other words, other budget components make most of the adjustments required to balance spending and revenue).…”
Section: The Impact Of the Total Amount Of Aid On Public Social Expenmentioning
confidence: 98%